Innovative model of annular fuel design for lead-cooled fast reactors - Rowinski, Marcin Karol (2015)
The results of an investigation of the analytical solutions of the default – solid fuel and innovative – annular fuel approach are summarized in this paper. Innovative annular fuel concept is described in details and shows that it is a promising technology in terms of safety aspects. Liquid metal cooled reactors are considered to burn used nuclear fuel from conventional nuclear power plants or processed weapon grade plutonium and therefore, higher safety standards must be assured.